2021
DOI: 10.1007/s12024-021-00355-3
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA collection from police dogs: technique and application

Abstract: Police dogs are routinely deployed during criminal investigations under a variety of circumstances. In instances where police dogs are involved in apprehension of suspects, contact with a suspect may be observed or may occur out of the line of sight. The interactions between suspect and dog may include the dog biting the suspect, or the suspect touching or exuding bodily fluids onto the dog. In either form of contact, potentially valuable DNA may be left from the suspect on the dog. This paper describes a proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…While the results from the small-scale study by Brower et al [11] indicate that human DNA can be obtained from some areas of dogs in certain situations, the extent of human DNA TPPR relating to dogs may be dependent on various factors, including the shedder status of the humans that a dog comes into contact with [12][13][14] and the frequency and manner of interactions they have with a dog [15,16]. As such, it is clear that more extensive investigations are required in respect to human DNA TPPR relating to dogs.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…While the results from the small-scale study by Brower et al [11] indicate that human DNA can be obtained from some areas of dogs in certain situations, the extent of human DNA TPPR relating to dogs may be dependent on various factors, including the shedder status of the humans that a dog comes into contact with [12][13][14] and the frequency and manner of interactions they have with a dog [15,16]. As such, it is clear that more extensive investigations are required in respect to human DNA TPPR relating to dogs.…”
Section: Introductionmentioning
confidence: 93%
“…To the authors' knowledge, there has only been one study thus far that has investigated the recovery of human DNA from dogs. As part of their study, Brower et al [11] investigated the extent to which human DNA could be recovered from separate samples taken from the muzzle hair and teeth of a dog 2 min after a person handled the muzzle and rubbed the surfaces of the incisor and canine teeth, and again from another dog 15 min after the muzzle/teeth area was handled. Partial human DNA profiles were generated from hair and teeth samples obtained at 2 and 15 min post-handling; however, it was not clear who the source of the DNA was (i.e., the handler, the owner, or other).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies continue to elucidate the ability to generate DNA profiles from samples taken from touched objects [61][62][63][64]. Additional studies evaluated means of generating human DNA profiles from traces of biological material left on various items, includ-ing hair [65], bricks [66], dogs [67], bite marks in food [68], paper documents [69], eye wear [70], superabsorbent polymer-containing products (commonly found in nappies and sanitary towels) [71], improvised explosive devices [72], rifle magazines [73] and bullet cartridges [74][75][76][77][78]. Further, Gray et al [79] demonstrated that STR DNA profiles can be generated from human blood found in Anopheles mosquitoes, from one or multiple individuals, and that the quality of the profiles declined as the duration between mosquito blood meal and sample collection increased.…”
Section: Samplingmentioning
confidence: 99%